2012
DOI: 10.1534/g3.112.004051
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms Contribute to Lateral Transfer of an Organophosphate Degradation (opd) Island in Sphingobium fuliginis ATCC 27551

Abstract: The complete sequence of pPDL2 (37,317 bp), an indigenous plasmid of Sphingobium fuliginis ATCC 27551 that encodes genes for organophosphate degradation (opd), revealed the existence of a site-specific integrase (int) gene with an attachment site attP, typically seen in integrative mobilizable elements (IME). In agreement with this sequence information, site-specific recombination was observed between pPDL2 and an artificial plasmid having a temperature-sensitive replicon and a cloned attB site at the 3′ end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…The first example of a sequenced and carefully analysed degradative plasmid from a sphingomonad was plasmid pNL1 from Sphingomonas (now Novosphingobium) aromaticivorans F199, which carries all genes required for the degradation of biphenyl, naphthalene, m-xylene and p-cresol . Subsequently, the sequence analysis of plasmids pCAR3 (carrying all the genes for the mineralization of carbazole), pCHQ1 (coding for the linRED genes participating in the degradation of c-hexachlorocyclohexane) and pPDL2 (coding for a parathion hydrolase involved in organophosphate degradation) has been published (Shintani et al, 2007;Nagata et al, 2011;Pandeeti et al, 2012; Table 1).…”
Section: Sequenced (Degradative) Plasmids From Sphingomonadsmentioning
confidence: 99%
“…The first example of a sequenced and carefully analysed degradative plasmid from a sphingomonad was plasmid pNL1 from Sphingomonas (now Novosphingobium) aromaticivorans F199, which carries all genes required for the degradation of biphenyl, naphthalene, m-xylene and p-cresol . Subsequently, the sequence analysis of plasmids pCAR3 (carrying all the genes for the mineralization of carbazole), pCHQ1 (coding for the linRED genes participating in the degradation of c-hexachlorocyclohexane) and pPDL2 (coding for a parathion hydrolase involved in organophosphate degradation) has been published (Shintani et al, 2007;Nagata et al, 2011;Pandeeti et al, 2012; Table 1).…”
Section: Sequenced (Degradative) Plasmids From Sphingomonadsmentioning
confidence: 99%
“…Both the opd and mpd genes are carried on a mobile genetic element. Identical opd and mpd genes are found among taxonomically unrelated soil bacteria [4][5][6], and even dissimilar indigenous plasmids found in bacteria isolated from diverse geographical regions contain identical opd gene clusters [7]. There are four indigenous plasmids in OP-degrading Sphingobium fuliginis ATCC 27551 [8], one of which, the opd-containing pPDL2, has been shown to be a mobilizable plasmid within which the opd region has unique organizational features [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…to protocatechuate degradation, the opd gene forms part of an active transposon [6]. The mobilizable plasmid also contains an integrase and an attachment (attB) site that facilitate site-specific integration, and recent studies have shown its ability to integrate at an artificially created attB site.…”
Section: Introductionmentioning
confidence: 99%
“…Further study of the purported opd transposon on pPDL2 of S. fuliginis ATCC 27551 has confirmed that the gene lies on a catabolic transposon along with genes that encode for aromatic transporter proteins and protocatechuate dioxygenase. The authors have also identified an integrase that allows for lateral integration into a new host chromosome should the organism be unable to replicate the pPDL2 plasmid providing a likely explanation for the gene's sudden emergence in many new genera of soil bacteria (Pandeeti et al ., ). Furthermore, the closest homologues of the insertion operon and transposase found within the opd gene clusters on these plasmids are also found in strains of A. tumefaciens , and with the discovery of the aforementioned opdA gene reported from a strain of A. radiobacter , this could indicate an evolutionary origin in Agrobacterium (Horne et al ., 2002a; Siddavattam et al ., ).…”
Section: The Opd Gene and Organophosphorus Hydrolasesmentioning
confidence: 97%